Combustion Characteristics of Coated Nano Aluminum in Composite Propellants - Sun, Yunlan; Li, Shufen (Defence Science Journal, 2006)
The effects of coated nano-sized aluminum (Al) powder (n-Al) and micron-sized Al powder (g-Al) in propellants on the burning rate and pressure exponent have been investigated. The results show that the burning rates of propellants increase as the n-Al content increases, but the burning rate pressure exponents tend to decrease. Compared with propellant containing -Al, the increments of burning rates of propellants containing n-Al powder reduce gradually with increase in the pressure because of the differences of the combustion characteristics and ignition performances of n-Al powder and g-Al powder. Single short distance photograph, scanning electron microscopy, x-ray fluorescence analysis were used to characterise the flame image, combustion phenomena, the quenched surface image, and surface elements. A substantial difference in combustion characteristics of n-Al powder has been found in comparison with -Al powder. In addition, oxygen-bomb combustion heat, ignition temperature, and recovery ratio of residues were measured.